Air Pollution Trends In Petaling Jaya, Selangor, Malaysia - Amir, Amnorzahira (2007)

(untitled)
Petaling Jaya experiences the worst air pollution in the Klang Valley. The main source of air pollution in Petaling Jaya is found to be from vehicular exhaust. This is because Petaling Jaya is a mixed commercial-residential-industrial area which has the highest population in the Klang Valley. Moreover, the industrial area in Petaling Jaya is surrounded by the residential area. These factors are believed to be one of the contributors for air pollution in Petaling Jaya. In addition to these, there are universities, colleges and schools in this area. Hence, it is important to monitor the air quality in Petaling Jaya. An investigation of trends for major air pollutants such as particulates matter (PM10), carbon monoxide (CO), sulfur dioxide (SO2), nitrogen dioxide (NO2), and ozone (O3) in compliance with Recommended Malaysia Ambient Air Quality Guidelines (RMAAQG) and Air Pollutant Index (API) analysis have been carried out to identify the main pollutant in Petaling Jaya for the year 2005. From this analysis, PM10 has been identified as the main pollutant contributes to the API value. Therefore, PM10 is the main pollutant for year 2005 in Petaling Jaya. The relationships between pollutant-pollutant and pollutant-meteorological parameter are also being investigated by using matrix correlation and wind sector analysis. From the matrix correlation analysis, there is a high correlation between PM10-CO (R=0.78) which indicates that they originate from the common source which is vehicle exhaust. The correlations between O3-Temperature (R=0.40), O3-NO2 (R=0.24), and NO2-Temperature (R=0.06) illustrate that the photochemical reaction occur actively in the urban area atmosphere such as Petaling Jaya. The findings also indicate that rainfall and wind speed also influence the PM10, SO2, CO and NO2 concentration by the washout and dilution effect but their correlations are low. Wind sector analysis reveals that wind direction plays an important role in pollutants distribution. The pollutants concentration is distributed differently according to wind direction. In this analysis, North-East and South-West direction experience high pollutants concentration especially for PM10 and CO. More interesting, the correlation between PM10-CO at these directions is high which is 0.5 and 0.6 respectively. This indicates that they originate fully from the common source which is vehicle exhaust in these wind directions. However, there are still unknown sources for PM10 (15.5 μg/m3) in Petaling Jaya. On the other hand, concentrations for NO2, SO2 and O3 are quite similar at North-East, South-East and South-West directions. In conclusion, meteorological conditions play an important role in influencing the air pollutants concentration in Petaling Jaya.